STUDI PEMANFAATAN CANGKANG KEPITING (Scylla sp.) UNTUK FILTER AIR TANAH DI KOTA TARAKAN - Syamsiah, Syamsiah; Achyani, Ratno; Irawati, Heni (Universitas Borneo Tarakan, 2023)
The city of Tarakan has the potential of ground water for clean water needs. But for its use, it nedds to be treated first so that the quality is in accordance with the required quality standards. Crab shell (Scylla sp.) waste is used as a filtration technology for water treatment. The purpose of this research was to study the effetiveness of using crab shells as a ground water filter in Tarakan City. The research method used in this study was an experimental method with a complete random design (RAL). Repetition was done three times. The material used was crab shell with a filter level of 30, 60 and 100 cm. Crab shells were combined with the use of activated charcoal, quartz sand and gravel to determine the best composition. The parameters that were tested according to the Regulation of the Minister of Health No. 32 of 2017 (Water Quality Standards for Sanitary Hygiene Needs) are turbidity, color, odor, pH, Temperature, TSS, TDS, nitrate, nitrite, iron (Fe) and manganese (Mn). The study’s findings demonstrated that the crab shell’s filtering effectiveness is quite low. For the pH parameter, the effectiveness value increased succcessively based on the filter level of 30,60 and 100 cm which was 54, 71, 80% and the Mn paraneter successively was 74, 92 and 81%. While the parameters of turbidity, color, TDS, TSS, nitrite, nitrate, and iron actually decreased the value of water quality, when compared to the value of standard water.